Molecular detection of Mycobacterium tuberculosis from bovine milk samples (Journal of Advanced Veterinary and Animal Research, 2014)
Mycobacterium tuberculosis and Mycobacterium bovis are the major causes of tuberculosis. These may infect many animal species, and are likely to be the main source of infection in humans. A total of 181 bovine raw milk samples and 123 pre-scapular lymph node biopsy samples were collected and subjected to acid fast staining, fluorescent staining, isolation and identification. Genus specific PCR to identify the Mycobacterium tuberculosis complex (MTBC) organism, and multiplex PCR (mPCR) were done to differentiate M. tuberculosis and M. bovis. Among the milk samples tested, only one sample was culturepositive for M. tuberculosis. Four samples were positive by MTBC-PCR and mPCR; all these four were proved to be M. tuberculosis. It is quite likely that animals can be infected with human-originated M. tuberculosis, which in turn may act as a source of infection in humans, becoming a reverse zoonosis. Hence, control strategies for human tuberculosis caused by M. tuberculosis should necessarily include the control strategies in animals too. http://dx.doi.org/10.5455/javar.2015.b44